Seasonal differences to the effect of nematode parasitism on weight gain of sheep and goats in Cigudeg, West Java - Beriajaya I; D.B Copeman (Jurnal Ilmu Ternak dan Veteriner, 1996)
This study was designed to investigate the seasonal effect of gastrointestinal nematode parasitism on weight gain of recently weaned sheep and goats in an area of West Java. Most animals were allowed to graze during the day and kept in pens with a raised slatted floor during the night Three trials were conducted in tandem,each for a period of4 months . The effect of parasitism was assesed by comparing weight gain of untreated animals with that of otherwisesimilar group treated each 2 weeks with oxfendazole or albendazole to suppress nematode parasitism . There was no difference between weight gain of treated and untreated sheep and goats during the dry season . Moreover, during the dry season both treated and untreated sheep and goats grew at about twice the rate of untreated animals and 25 percent greater than treated animalsduring the wet season . As faecal egg counts (and, thus, presumably the level of parasitism) were the same throughout the year it was concluded that the low level of nutrition during the wet season was the main determinant affecting pathogenicity of gastrointestinal nematode parasitism in this study. Furthermore, improved nutrition during the wet season in areas similar to that of this study, especially in sheep and goats for the first 10 weeks after weaning, may obviate the need for anthelmintic therapy, being a means to both increase weight gain and negate the effect of nematode parasitism   Key words: Sheep, goat, oxfendazole, albendazole, nematode parasitism